Outcome after practical isthmus ablation of scar-related atrial tachycardia guided by high-density mapping. (25th November 2020) - Jungen, C; Akbulak, R; Kahle, A; Eickholt, C; Schaeffer, B; Dinshaw, L; Schleberger, R; Nies, M; Gunawardene, M; Muenkler, P; Klatt, N; Hartmann, J; et al.
Abstract: Background: High-density mapping (HDM) has been found to precisely identify the practical isthmus of scar-related atrial tachycardia (AT) circuits. Since practical isthmuses have been found to be shorter than the usual anatomical isthmuses targeted ablation has been proposed. However, outcome data are sparse. Here we describe HDM-guided catheter ablation by targeting the practical isthmus in patients with scar-related ATs. Methods and results: In 250 consecutive patients with scar-related ATs HDM-guided catheter ablation with the support of a 64-electrode mini-basket catheter has been performed. Most patients underwent a prior catheter ablation (98%) while 13% had a prior cardiac valve surgery and 6% an underlying congenital heart disease. A total of 355 ATs occurred in the index procedure, of which 64% had a macro-, 26% a micro-reentry and 10% a focal mechanism. The ATs had a mean cycle length of 304±4.3 ms and in 237 patients (95%) an acute termination into sinus rhythm was achieved. They were mainly located in the left atrium (72%) but also in the right atrium (25%), bi-atrially (5%) or in the CS (3%) (see figure). Targeting the practical isthmus revealed arrhythmia freedom in 53% of patients after a single procedure during a mid-term follow-up (median 489 days, range 95–1407 days). Freedom from any arrhythmia could be achieved in 74% of patients after multiple procedures and in 93% of patients after multiple procedures and optimal clinical therapy, including pharmaceutical or electrical cardioversion. Conclusions: HDM-guided catheter ablation of the practical isthmus in patients with scar-related ATs leads to a high acute success rate. Nevertheless, multiple procedures are necessary in a relevant number of patients resulting in a low recurrence rate. Funding Acknowledgement: Type of funding source: None